Determination of Electrospinning Parameters' Strength in Poly(D, L)-lactide-co-glycolide Micro/Nanofiber Diameter Tailoring. (28th January 2019) - Chen, Yi-Pin; Liu, Hsin-Yi; Liu, Yen-Wei; Lee, Tzung-Yan; Liu, Shih-Jung
Abstract : Electrospinning has received increasing interest and attention in recent years for fabricating micro/nanofibers of various materials; this is due to its versatility and capability of multiple field applications, including filtration, biosensors, tissue engineering, wound dressings, drug delivery, and composites. Nonetheless, the optimization of the electrospinning process is based on a time-consuming trial-and-error procedure. An empirical study, in conformity with the Taguchi orthogonal matrix design, was carried out to investigate the influence of various processing variables on the electrospinning of resorbable poly(D, L)-lactide-co-glycolide (PLGA). Three different solvents, hexafluoro-2-propanol (HFIP), dichloromethane (DCM), and trichloromethane (TCM), were employed. Five variables were selected for evaluation, including PLGA concentration, the solution's flow rate from the nozzle, the distance between the nozzle and ground collection, the voltage, and the type of solvents. After electrospinning, we performed a morphological analysis of nanofibers by scanning electron microscopy (SEM) and measured the fiber size by the evaluation of SEM images. Among the variables selected, the type of solvent and the applied voltage were found to be the principal variables influencing the diameter distribution of electrospun PLGA fibers. Nanofibers with the smallest fiber size (466.25 ± 158.38   n m ) could be obtained with HFIP solvent and an applied voltage of 15 kV.